A Systematic Review of Elective Laser Therapy during Pregnancy: Laser Therapy During Pregnancy - Allameh, Farzad; Javadi, Atefeh; Dadkhahfar, Sahar; Naeeji, Zahra; Moridi, Atefeh; Tadayon, Niki; Alahyari, Sam (Journal of Lasers in Medical Sciences, 2021)
Introduction: Currently, lasers are used to treat many diseases and their complications. However, the use of lasers in pregnant patients is still controversial. Methods: In this review, the application of lasers in the fields of urology, surgery, obstetrics, dermatology, and musculoskeletal disorders is evaluated. The following keywords were used to search through PubMed, Google Scholar, and Scopus: pregnancy, laser, urolithiasis, endovenous laser ablation (EVLA) or treatment, leg edema, varicose vein, venous insufficiencies, hair removal, pigmentation, telangiectasia, vascular lesions, Q switch laser, diode laser, holmium, holmium-YAG laser, erbium laser and Pulsed dye laser, low-level laser therapy, high-intensity laser therapy, pain, musculoskeletal disorders, twin to twin transfusion syndrome (TTTS), amnioreduction, and safety. Results: Totally, 147 articles were found, and their abstracts were evaluated; out of 53 articles extracted, 14 articles were about dermatology, 24 articles were about urology, 12 articles were about obstetrics and gynecology, 10 articles were about musculoskeletal disorders and three articles were related to surgery. Conclusion: Laser therapy can be used as a safe treatment for urolithiasis, skin diseases, TTTS, and varicose veins of the lower extremities. However, the use of laser therapy for musculoskeletal disorders during pregnancy is not recommended due to lack of evidence, and also we cannot recommend endovenous ablation. DOI: 10.34172/jlms.2021.50